Human emotional evaluation of ancestral and modern threats: fear, disgust, and anger - Peléšková, Šárka; Polák, Jakub; Janovcová, Markéta; Chomik, Aleksandra; Sedláčková, Kristýna; Frynta, Daniel; Landová, Eva (Frontiers in Psychology, 2024)
Introduction Animal and human ancestors developed complex physiological and behavioral response systems to cope with two types of threats: immediate physical harm from predators or conspecifics, triggering fear, and the risk of infections from parasites and pathogens leading to the evolution of the behavioral immune system with disgust as the key emotion. Integration of the evolutionary concepts of the fear module and behavioral immune systems has been infrequent, despite the significant survival advantages of disgust in various contexts. Studies comparing attention to ancestral and modern threats accompanied by fear have yielded ambiguous results and what qualifies as salient modern disgusting stimuli remains unclear. We do not know whether disgust or the behavioral immune system, as inherent aspects of human psychology, have adapted to safeguard us from pandemic risks or poisoning by modern toxic substances. Methods To test these effects, we have developed a survey comprised of 60 short vignettes describing threats evoking fear and disgust belonging to one of the three main categories of threats: (1) ancestral (phylogenetic), (2) modern (ontogenetic), and (3) pandemics of airborne disease. Each vignette was evaluated on a 7-point Likert scale based on fear, disgust, and anger. In total, 660 respondents completed the survey. The data were analysed using a factor analysis and general linear model with the respondent as a random factor. Results The results show that the strongest fear is triggered by modern threats (electricity, car accidents), while the highest disgust is evoked by ancient threats (body waste products, worms, etc.). Interestingly, disgust does not respond to modern threat stimuli such as toxic substances or radioactivity as these evoke mainly fear and anger. Finally, a distinct response pattern was found for pandemic threats, in which both fear (e.g., of disease and death) and disgust (e.g., of used face masks) are employed. Discussion Our study offers valuable insights into the emotional responses to ancestral and modern threats and their adaptation to pandemic challenges. Ancestral threats are not always more powerful stimuli than adequate threats of the modern type, but they function specifically. Thus, snakes and heights as fear-inducing ancestral threats form separate factors in a multivariate analysis, whereas all ancestral disgust stimuli group together. The threat of a pandemic forms a specific category and people process it emotionally and cognitively. These insights contribute to our understanding of human psychology and behavior in an ever-changing world.